2004
DOI: 10.1023/b:wate.0000038903.25700.5a
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Determination in Atmospheric Deposition and Other Fluxes in Northern France Agrosystems

Abstract: International audienceThe aim of this study is to assess the annual balance of the fluxes of Cd, Cu, Ni, Pb and Zn within different cropping systems, in an experimental site located near Versailles, France. Four fluxes through the cultivated horizon were considered to assess the annual heavy metal balance in these systems: 1) atmospheric depositions, 2) fertilisers as inputs, 3) crops and 4) leaching water as outputs. The water mass flow was estimated with a model (CERES) while the other parameters were actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
1
20
3
1
Order By: Relevance
“…In NP and NPK treatments, except for Fe, balances for Mn, Zn and Cu were negative, suggesting the need for supplementation of these micronutrients for sustainable crop production. In this study, the input of micronutrients from the atmospheric deposition was low as compared to organic manure input; however, previous studies have shown that deposition was an important source for the agroecosystem and accounted for 20-80 % of the total input (Azimi et al 2004;Ali-Khodja et al 2008). The results of our study showed that the balances of micronutrients were negative without fertilizer and manure applications.…”
Section: Balances Of Micronutrientscontrasting
confidence: 49%
See 1 more Smart Citation
“…In NP and NPK treatments, except for Fe, balances for Mn, Zn and Cu were negative, suggesting the need for supplementation of these micronutrients for sustainable crop production. In this study, the input of micronutrients from the atmospheric deposition was low as compared to organic manure input; however, previous studies have shown that deposition was an important source for the agroecosystem and accounted for 20-80 % of the total input (Azimi et al 2004;Ali-Khodja et al 2008). The results of our study showed that the balances of micronutrients were negative without fertilizer and manure applications.…”
Section: Balances Of Micronutrientscontrasting
confidence: 49%
“…Concentrations of micronutrients in commercial K and N (urea) fertilizers are not well documented, and little attention has been given to their application compared to the applications of superphosphate and organic manures in terms of the availability of micronutrients. More recent researches have indicated a rising trend in atmospheric deposition of nutrients and toxic metals in different parts of the world, including the Indian subcontinent (Patel et al 2001;Azimi et al 2004;Singh and Agrawal 2005). Keller et al (2001) pointed out the relative importance of atmospheric deposition for heavy metal input in arable ecosystems.…”
Section: Introductionmentioning
confidence: 97%
“…The lowest excess of each micronutrient consistently occurred in the NPK treatment. While the input ratios of micronutrients deposition were higher in our study, previous studies have shown that deposition was an important source for the agro-ecosystem and accounted for 20-80% of the total input (Ali-Khodja et al 2008;Azimi et al 2004). Luo et al (2009) concluded that some trace elements were accumulated in agricultural soils with increasing inputs through atmospheric deposition, feed additives, fertilizers, agrochemicals, sewage irrigation and sewage sludge excessive application.…”
Section: Balances Of Micronutrients In Arable Soilcontrasting
confidence: 45%
“…Zn appeared about twofold to tenfold higher than other elements in atmospheric deposition which are ranked in the order Cu> Pb> Ni> Cd (except for Pb during 1999 and2000). Such patterns have also been observed at other urban sites (Azimi et al 2003(Azimi et al , 2004. Since the air mass flow of the region is mainly from west and southwest to the east and northeast (Pandey 2005), the urban-industrial emissions could sizably contribute to atmospheric bulk deposition of the area.…”
Section: Discussionmentioning
confidence: 65%